Towards Sustainable Campus Development: A Case Study of Klaipeda University - Anne Olga; Mikalauskas Ignas (E3S Web of Conferences)
Klaipeda University (KU) has initiated a transformative project to create a green campus. This involves integrating renewable energy sources and smart building systems to improve resource efficiency and encourage sustainable living practices. An assessment of these initiatives examines their impact on sustainability, energy consumption, and educational outcomes. The evaluation involves a mixed-methods research approach, utilizing both qualitative and quantitative data from technical reports, system performance metrics, and academic literature. The findings reveal positive developments in energy management, with geothermal and solar energy systems significantly reducing the university's carbon footprint. The implementation of building management systems (BMS) has led to optimized energy usage, resulting in a decrease in environmental impact. Moreover, the green campus initiatives have enhanced the educational experience by promoting a culture of sustainability within the university community. This case study offers a valuable model for other regional institutions aiming to adopt similar sustainable practices and technologies, aligning with the United Nations Sustainable Development Goals (SDGs).